The Relationship between Sukuk Issuance and Its Determinants in Islamic Capital Market - Saad, Noriza Mohd (Journal of Posthumanism, 2024)
The objective of this study is to investigate the relationship between sukuk tenure and zakat investment with sukuk issuance influenced by systematic risk factors. Secondary data were utilized from 2000 to 2023 for 2840 observations. Results from regression tests reported that the maturity date or tenure of sukuk has a significant positive relationship towards its issuance in all equation model regressions for the fixed effects, random effects, and robust effects models. However, zakat investment is significant only in the random effects model, justifying the wealth contribution paid for profitable investment/project at a specified date. All systematic risk factors showed a significant effect towards sukuk issuance, with mixed positive and negative associations, except for interest rate spread. Thus, to encourage sukuk issuance by companies or the government, the issuer need to closely monitor the sukuk tenure to reduce risk and make a decision in paying zakat investment for business sustainable in future.